(untitled) (Journal of the College of Basic Education, 2026)
Nowadays, students feel free to apply various sources of obtainable online information because of their ease of access and availability. Any source of AI tools for EFL students is allowed to be used by students .These new tools help students develop their academic accomplishment and expertise. The study aims to show whether AI tools have a negative or positive impact on students’ retention of reading comprehension. 80 Third- year non-English students at Al Mustansiriyah University participated in the study .They were assigned into two groups: the first is the experimental group, and the second is the control group. The experimental group was taught reading using SQ3R (survey, question, read, recite ,and review)strategy along with AI tools, while the control group was taught using SQ3R strategy and too a test without the use of AI tools .In the current study, a one way ANOVA was used. The study follows a quasi-experimental design, which is a non-randomized control group posttest design. It is hypothesized that there is no statistically significant difference in the mean score of the students’ retention of reading comprehension who are taught using AI tools and those who are taught according to the traditional method. The study’s results indicated that students in the experimental group achieved better outcomes than the students in the control group as shown by evaluation of their test scores .In addition ,the study revealed that combining AI tools demand not only information of technological tools but educational orientation that connects them with learning results .The study concludes that applying AI tools inside class draw a pedagogical tool that motivates students’ psychological aspects to find out the most suitable answer as soon as possible .At the end of this current study, recommendations concentrate on future researches should be put forward.